Detailed Land Cover and Land Use Mapping, A New Approach: Case Study, Usumacinta Watershed, Mexico - Daniel, López L.; Aristides, Saavedra G (British Journal of Healthcare and Medical Research, 2024)
Land use system is the interface between society and the biophysical environment; it is concern how humans use ecosystems services provide by natural resources. Land-use and land-cover changes have great effects for the environmental and socioeconomic sustainability of rural communities. A capacity for detecting and reporting land use change is critical to evaluating and monitoring trends in natural resource conditions and the effectiveness of public investment in their management. In Mexico, despite ongoing mapping land use - land cover efforts; there remains a need for development of basic datasets providing quantitative and spatial land use/land cover information, mainly a detailed scale. Recent availability of high-resolution satellite remote-sensing images coupling with advances digital image processing techniques offers an improved opportunity to map in a more detailed scale the land use and land cover, which will be an important tool to monitor the environment at local scales. It is the objective of this study, conduct a detailed mapping of land use-land cover in Usumacinta watershed, using high-resolution satellite images and analyze changes occurred when is compared with National Institute of Statistic and geography map - Series VII,2016. The basis for the land use and vegetation cover presented in this study is the digital land cover and land use classification elaborated with SPOT imagery, spatial resolution 1.5 meters, using an object-based classification method in combination with an image classification based on expert knowledge. The resulting map was updated using Sentinel images 2021 and 2022 , by means of on screen digital interpretation. The result is a detail map of land use land cover, where new classes were generated as association and consociation units. As a conclusion is established that the resulting map is more stable in time, and it can be used as indicative to implement restoration measures on natural vegetation and as input to calculate a more precise estimations of agriculture statistic’s. All of this aspects can guide the design and implementation of public policies about land use.